Gender and Vascular Complications in the JAK2 V617F-Positive Myeloproliferative Neoplasms. (24th July 2011) - Stein, Brady L.; Rademaker, Alfred; Spivak, Jerry L.; Moliterno, Alison R.
Abstract : We previously found that gender influenced the JAK2 V617F allele burden, but it is unknown whether this gender difference in molecular epidemiology influences complications in the myeloproliferative neoplasms (MPNs). Historically, vascular complications represented the most common cause of mortality in polycythemia vera and essential thrombocytosis and contributed to morbidity in primary myelofibrosis. To determine the influence of gender on vascular complications, we retrospectively analyzed associations between gender and vascular complications. Despite their younger age, less prevalent dyslipidemia or smoking history, lower white blood counts, and lower JAK2 V617F allele burden, women had higher rates of abdominal venous thrombosis and comparable rates of all vascular complications. Vascular risk is currently not easily stratified by MPN-disease burden or traditional risk factors. Our analysis contributes to growing literature emphasizing gender differences in the MPN and further supports the important impact of individual and host variation on MPN clinical manifestations, and especially vascular risk.